Congenital syphilis in Switzerland: a marker of inequality? A mini-review - David, Antoine; Posfay-Barbe, Klara M.; Aguiar Nogueira, Carina; Toutous Trellu, Laurence (Frontiers in Public Health, 2023)
Syphilis remains a global public health problem, with growing incidence in most regions of the world, particularly among women of childbearing age. This alarming trend has led to an increase in cases of congenital syphilis, resulting in devastating consequences. While the implementation of measures by the World Health Organization (WHO) and various governments has contributed to a decline in the global incidence of congenital syphilis, many countries are facing an escalating crisis, as incidence continues to rise. This mini-review aims to provide an overview of the current state of this disease in different parts of the world, focusing on the most affected populations and highlighting congenital syphilis as a marker of vulnerability. It also focuses on Switzerland, a country with a robust economy, to identify shortcomings in the healthcare system that contribute to the persistence of congenital syphilis, even though the infection is easily detectable and treatable. In conclusion, this mini-review highlights the persistent risk of congenital syphilis worldwide, regardless of country prevalence or economic status, and underscores the need for sustained efforts to reach underserved women, emphasizing the vital role of comprehensive training for healthcare professionals.